GENETIC DIVERSITY OF MACKEREL SCADS, Decapterus macarellus (Cuvier, 1833) IN THE INDIAN OCEAN - Achmad Zamroni; Suwarso Suwarso (Indonesian Fisheries Research Journal, 2017)
Mackerel scads (Decapterus macarellus) is a small widely distributed pelagic species in ocean. In 2013, monthly catch and abundance index of mackerel scads increased in western part of Sumatera waters. High exploitation of mackerel scads may lead to decrease stock due to the over exploitation. Stock information is very useful for calculating of the potential fish. Genetic analysis is one of the powerful tools to estimate fish stock quickly. Genetic diversity of mackerel scads in this study was analyzed using RFLP (Restriction Fragment Length Polymorphism) with AfaI, EcoR I, HapII, HinfI and TaqI restriction enzyme. The results showed that the lowest genetic diversity of mackerel scads was Labuan population. Kinship Labuan was also the furtherest stock compared to other populations. It can be concluded that the population of Labuan is derived from a different sub-species. The closest kinship was between Aceh and Sibolga stock.